PENGARUH RELIGIUSITAS TERHADAP KECERDASAN EMOSIONAL PESERTA DIDIK: DI MA SERBA BAKTI SURYALAYA TASIKMALAYA - Nur’aisyah, Ai; Djamad, Ahmad (THORIQOTUNA: Jurnal Pendidikan Islam, 2019)
The study aims of to describe and analyze the influence ofreligiosity toward emotional intelligence of learners. This research usesdescriptive method through a quantitative approach. With a populationof 305 , with a sample of 32 . The technic Sampling was done byPurposive sampling. The collection of data through observation sheets,questionnaires, and interviews, as well as processing quantitative datais solved by the formula of Spearman Rank (rs). The results ofSpearman Rank correlation of 0.60 understood that the influence ofReligiosity toward Emotional Intelligence of learners is quite, theresults of hypothesis testing where t is 4.11, while table 2,042. Based onthat reality, then the alternative hypothesis (Ha) states that there is asignificant positive correlation regarding the influence of religiositytoward emotional intelligence students accepted, then H0 is rejected.The influence is 36%, and rest by other factors, which amounted to64%.